Network characteristics of referrals for chronic disease patients: results from hierarchical medical reform in Shenzhen, China - Fangfang Gong; Junxia Luo; Zhihong Wang; Ping Tang; Guangyu Hu; Ying Zhou; Hanqun Lin (BMC Public Health)
Abstract Background The Chinese government has introduced a series of hierarchical medical policies to ensure continuity of care, but referrals remain difficult to implement effectively. This study aimed to evaluate the chronic disease referral network and explore the problems associated with the specific implementation of referrals. Methods This study was a repeated cross-sectional study of monthly data collected between August 2017 and December 2023 in Luohu district, Shenzhen, China. Social network analysis was used to construct a referral network for chronic disease patients. Density, degree centrality, and betweenness centrality were calculated to assess the relationships and status among different levels of care and their trends. Results Over seven years, 104,682 chronic disease patients were referred, with a predominance of downward referrals. The number of upward referrals (Z = 2.5776, P trend < 0.01) and downward referrals (Z = 4.7723, P trend < 0.001) increased significantly. Primary care facilities (PCFs) were strongly associated with the tertiary hospital (0.51–0.98). The out-degree of all levels of medical institutions showed a significant increasing trend (P trend < 0.05). The coronavirus disease 2019 (COVID-19) pandemic did not cause significant level changes in network metrics but accelerated the upward trend in the out-degree of secondary hospitals (P < 0.05). The in-degree of secondary hospitals and PCFs showed a significant increasing trend (P trend < 0.01). Public PCFs had significantly higher network metrics compared to private PCFs (P < 0.001). Conclusions The referral network has a vertical flow pattern conducive to the division of labour, cooperation, and resource integration of medical institutions in the region, and a hierarchical medical order is taking shape. However, poor communication between secondary hospitals and other institutions, high demand for data informatisation, and the gap between private and public PCFs may hinder further progress.